A review of antifungal activity of bacterial strains and their secondary metabolites against Fusarium species - Lais Sousa Almeida; Suzana Kaory G. Inoue; Joana Montezano Marques; Joyce Kelly R. da Silva (Reviews in Environmental Science and Bio/Technology, 2025)

Alien toxic toads suppress individual growth and phenotypic development of native predatory salamanders - Yoshihiro Inoue; Hisanori Okamiya; Takayuki Aota; Michael R. Crossland; Osamu Kishida (Oecologia, 2025)

Hybridization and reticulate evolution in Diphasiastrum (flat-branched clubmosses, Lycopodiaceae) – New data from the island of Taiwan and Vietnam - M. Schnittler; M. Inoue; O.N. Shchepin; J. Fuchs; H. Chang; P. Lamkowski; R. Knapp; K. Horn; H.W. Bennert; M. Bog (Molecular Phylogenetics and Evolution, 2024)

Two Hidden mtDNA-Clades of Crown-of-Thorns Starfish in the Pacific Ocean - Nina Yasuda; Jun Inoue; Michael R. Hall; Manoj R. Nair; Mehdi Adjeroud; Miguel D. Fortes; Mutsumi Nishida; Nat Tuivavalagi; Rachel Ravago-Gotanco; Zac H. Forsman; Taha Soliman; Ryo Koyanagi; et al. (Frontiers in Marine Science, 2022)
Recurring outbreaks of crown-of-thorns starfish (COTS) severely damage healthy corals, especially in the Western Pacific Ocean. To obtain a better understanding of population genetics of COTS and historical colonization across the Pacific Ocean, complete mitochondrial genomes were sequenced from 243 individuals collected in 11 reef regions. Our results indicate that Pacific COTS ( Acanthaster cf. solaris ) comprise two major clades, an East-Central Pacific (ECP) clade and a Pan-Pacific (PP) clade, separation of which was supported by high bootstrap value. The ECP clade consists of COTS from French Polynesia, Fiji, Vanuatu and the Great Barrier Reef (GBR). The Hawaii population is unique within this clade, while California COTS are included in EPC clade. On the other hand, the PP clade comprises multiple lineages that contain COTS from Vietnam, the Philippines, Japan, Papua New Guinea, Micronesia, the Marshall Islands, GBR, Vanuatu, Fiji and French Polynesia. For example, a lineage of the PP clade, which has the largest geographic distribution, includes COTS from all of these locations. These results suggest two alternative histories of current geographic distributions of COTS in the Pacific Ocean, an ECP clade ancestry or Western Pacific clade ancestry. Although further questions remain to be explored, this discovery provides an evolutionary context for the interpretation of COTS population structure which will aid future coral reef research in the Pacific Ocean, and ultimately improve reef management of COTS.

Pollution and contamination level of Cu, Cd, and Hg heavy metals in soil and food crop - Ramlan; M. Basir-Cyio; M. Napitupulu; T. Inoue; A. Anshary; Mahfudz; Isrun; M. Rusydi; Golar; Sulbadana; R. Bakri (International Journal of Environmental Science and Technology, 2022)
We aimed to assess and observe the accumulation of Cu, Cd, and Hg heavy metals on land and the contamination of plant tissues in Grand Forest Park, Palu, Indonesia, and its surrounding areas. The method used was a mix between survey and investigation, integrating data on research findings from before 2013 to 2016 with data from 2018. The data were analyzed using a correlation test, and descriptive statistics are presented in the form of tables and graphs. The results show that the highest concentration of Hg was found in the Poboya processing area (575.16 ppm) in 2013, though it gradually decreased to 287.64 ppm in 2018. The results of the Spearman’s rank test at the ∝ 0.05 level between average Cu land and Cu plant concentrations show that the obtained value ( r ) was 0.52 with a rho (ρ) of 0.13, which is not significant ( ρ 0.13 > 0.05), while for Cd and Hg metals, the obtained r values were 0.88 and 0.86, respectively. These two metals showed significant correlations between concentrations of Cd and Hg on land and Cd and Hg in plant tissues (both ρ 0.001 < 0.05). Specifically, the transfer factor (TF) value at the sampling sites of the Grand Forest Park area, Ngatabaru, and PBY from the average of various Hg concentrations in plants was much higher than the TF values of Cu and Cd, specifically being Hg > Cd = Cu or 0.61 > 0.17 = 0.17.

Area-wide insecticide resistance and endosymbiont incidence in the whitefly Bemisia tabaci MEAM1 (B biotype): A Neotropical context - R. A. C. Dângelo; M. Michereff-Filho; A. K. Inoue-Nagata; P. S. da Silva; M. Chediak; R. N. C. Guedes (Ecotoxicology, 2021)

Genetics of mouse behavioral and peripheral neural responses to sucrose - Cailu Lin; Masashi Inoue; Xia Li; Natalia P. Bosak; Yutaka Ishiwatari; Michael G. Tordoff; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Genetic controls of Tas1r3-independent sucrose consumption in mice - Cailu Lin; Michael G. Tordoff; Xia Li; Natalia P. Bosak; Masashi Inoue; Yutaka Ishiwatari; Longhui Chen; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Enhanced vertical turbulent nitrate flux in the intermediate layer of the Kuroshio in the Tokara Strait - T. Tanaka; D. Hasegawa; I. Yasuda; D. Yanagimoto; S. Fujio; H. Nakamura; R. Inoue; J. Nishioka (Journal of Oceanography, 2021)

Medium- and long-term functional behavior evaluations in an experimental focal ischemic stroke mouse model - Juçara Loli de Oliveira; Marina Ávila; Thiago Cesar Martins; Marcio Alvarez-Silva; Elisa Cristiana Winkelmann-Duarte; Afonso Shiguemi Inoue Salgado; Francisco José Cidral-Filho; William R. Reed; Daniel F. Martins (Cognitive Neurodynamics, 2020)

Complete sequence of a new bipartite begomovirus infecting Sida sp. in Northeastern Brazil - M. A. Macedo; C. M. Rêgo-Machado; M. L. Maliano; M. R. Rojas; A. K. Inoue-Nagata; R. L. Gilbertson (Archives of Virology, 2020)

Integrative taxonomy reveals a new species of freshwater mussel, Potamilus streckersoni sp. nov. (Bivalvia: Unionidae): implications for conservation and management - Chase H. Smith; Nathan A. Johnson; Kentaro Inoue; Robert D. Doyle; Charles R. Randklev (Systematics and Biodiversity, 2019)

High-throughput sequencing reveals a novel closterovirus in arracacha (Arracacia xanthorrhiza) - Anelise F. Orílio; Rosana Blawid; Gabriela A. Costa; Suzane S. V. S. F. Gomes; Tatsuya Nagata; Nuno R. Madeira; Alice K. Inoue-Nagata; Renato O. Resende (Archives of Virology, 2018)

Characterization of tomato leaf curl purple vein virus, a new monopartite New World begomovirus infecting tomato in Northeast Brazil - M. A. Macedo; L. C. Albuquerque; M. R. Maliano; J. O. Souza; M. R. Rojas; A. K. Inoue-Nagata; R. L. Gilbertson (Archives of Virology, 2018)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The importance of primary inoculum and area-wide disease management to crop health and food security - A. Bergamin Filho; A. K. Inoue-Nagata; R. B. Bassanezi; J. Belasque; L. Amorim; M. A. Macedo; J. C. Barbosa; L. Willocquet; S. Savary (Food Security, 2016)

Genetic divergence of Chikungunya virus plaque variants from the Comoros Island (2005) - Caroline Wasonga; Shingo Inoue; Cecilia Rumberia; George Michuki; James Kimotho; Juliette R. Ongus; Rosemary Sang; Lillian Musila (Virus Genes, 2015)

The role of the hyporheic zone for a benthic fish in an intermittent river: a refuge, not a graveyard - R. Kawanishi; M. Inoue; R. Dohi; A. Fujii; Y. Miyake (Aquatic Sciences, 2013)

Further evidence reveals that okra mottle virus arose from a double recombination event - Leonardo C. Albuquerque; Silvia A. Aranha; Fernanda R. Fernandes; Alice K. Inoue-Nagata (Archives of Virology, 2013)

Further characterization of tomato-infecting begomoviruses in Brazil - Leonardo C. Albuquerque; Arvind Varsani; Fernanda R. Fernandes; Bruna Pinheiro; Darren P. Martin; Paulo de Tarso Oliveira Ferreira; Thaís Oliveira Lemos; Alice K. Inoue-Nagata (Archives of Virology, 2012)

Molecular and biological characterization of a new Brazilian begomovirus, euphorbia yellow mosaic virus (EuYMV), infecting Euphorbia heterophylla plants - Fernanda R. Fernandes; Leonardo C. Albuquerque; Cristiane L. de Oliveira; Andréa R. R. Cruz; Wesley B. da Rocha; Talita G. Pereira; Fernanda Y. B. Naito; Natália de M. Dias; Tatsuya Nagata; Josias C. Faria; Francisco M. Zerbini; Francisco J. L. Aragão; et al. (Archives of Virology, 2011)

Search in Solanum (section Lycopersicon) germplasm for sources of broad-spectrum resistance to four Tospovirus species - É. C. Dianese; M. E. N. Fonseca; A. K. Inoue-Nagata; R. O. Resende; L. S. Boiteux (Euphytica, 2011)

Isolation and characterization of 17 polymorphic microsatellite loci in the spectaclecase, Cumberlandia monodonta (Bivalvia: Margaritiferidae) - Kentaro Inoue; Gregory R. Moyer; Ashantyé Williams; Emy M. Monroe; David J. Berg (Conservation Genetics Resources, 2011)

Characterization of a member of a new Potyvirus species infecting arracacha in Brazil - A. F. Orílio; A. N. Dusi; N. R. Madeira; Alice Kazuko Inoue-Nagata (Archives of Virology, 2009)

Brugmansia suaveolens mottle virus, a novel potyvirus causing leaf mottling of Brugmansia suaveolens in Brazil - N. Lucinda; T. Nagata; A. K. Inoue-Nagata; R. B. Salaroli; E. W. Kitajima (Archives of Virology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Natural infection of Alternanthera tenella (Amaranthaceae) by a new potyvirus - A. M. R. Almeida; C. Y. Fukushigue; F. Sartori; E. Binneck; S. R. R. Marin; A. K. Inoue-nagata; C. M. Chagas; E. R. Souto; T. Mituti (Archives of Virology, 2007)

Undergraduate dental education on oral appliance therapy for obstructive sleep apnea at The University of British Columbia - Satoru TSUIKI; Fernanda R ALMEIDA; Alan A LOWE; Yuichi INOUE (Sleep and Biological Rhythms, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Oscillatory behavior of monsoon rainfall over Sri Lanka during the late 19th and 20th centuries and its relationships to SSTs in the Indian Ocean and ENSO - B. A. Malmgren; R. Hullugalla; G. Lindeberg; Y. Inoue; Y. Hayashi; T. Mikami (Theoretical and Applied Climatology, 2007)

Cospeciation in the triplex symbiosis of termite gut protists ( Pseudotrichonympha spp.), their hosts, and their bacterial endosymbionts - S. NODA; O. KITADE; T. INOUE; M. KAWAI; M. KANUKA; K. HIROSHIMA; Y. HONGOH; R. CONSTANTINO; V. UYS; J. ZHONG; T. KUDO; M. OHKUMA (Molecular Ecology, 2007)
A number of cophylogenetic relationships between two organisms namely a host and a symbiont or parasite have been studied to date; however, organismal interactions in nature usually involve multiple members. Here, we investigated the cospeciation of a triplex symbiotic system comprising a hierarchy of three organisms — termites of the family Rhinotermitidae, cellulolytic protists of the genus Pseudotrichonympha in the guts of these termites, and intracellular bacterial symbionts of the protists. The molecular phylogeny was inferred based on two mitochondrial genes for the termites and nuclear small‐subunit rRNA genes for the protists and their endosymbionts, and these were compared. Although intestinal microorganisms are generally considered to have looser associations with the host than intracellular symbionts, the Pseudotrichonympha protists showed almost complete codivergence with the host termites, probably due to strict transmissions by proctodeal trophallaxis or coprophagy based on the social behaviour of the termites. Except for one case, the endosymbiotic bacteria of the protists formed a monophyletic lineage in the order Bacteroidales, and the branching pattern was almost identical to those of the protists and the termites. However, some non‐codivergent evolutionary events were evident. The members of this triplex symbiotic system appear to have cospeciated during their evolution with minor exceptions; the evolutionary relationships were probably established by termite sociality and the complex microbial community in the gut.

Fluctuating serotonergic function in premenstrual dysphoric disorder and premenstrual syndrome: findings from neuroendocrine challenge tests - Y. Inoue; T. Terao; N. Iwata; K. Okamoto; H. Kojima; T. Okamoto; R. Yoshimura; J. Nakamura (Psychopharmacology, 2006)

Development of Stable Isotope Dilution Quantification Liquid Chromatography–Mass Spectrometry Method for Estimation of Exposure Levels of Bisphenol A, 4-tert-Octylphenol, 4-Nonylphenol, Tetrabromobisphenol A, and Pentachlorophenol in Indoor Air - K. Inoue; S. Yoshida; S. Nakayama; R. Ito; N. Okanouchi; H. Nakazawa (Archives of Environmental Contamination and Toxicology, 2006)

Expression of foreign type I ribulose-1,5-bisphosphate carboxylase/ oxygenase (EC 4.1.1.39) stimulates photosynthesis in cyanobacterium Synechococcus PCC7942 cells - T. Iwaki; K. Haranoh; N. Inoue; K. Kojima; R. Satoh; T. Nishino; S. Wada; H. Ihara; S. Tsuyama; H. Kobayashi; A. Wadano (Photosynthesis Research, 2006)

Effect of the protein kinase C inhibitor, staurosporine, on the high dose of methamphetamine-induced behavioral sensitization to dizocilpine (MK-801) - Y. R. Fang; T. Abekawa; X. B. Li; Z. C. Wang; T. Inoue; T. Koyama (Psychopharmacology, 2005)

Leptin and post-prandial satiety: acute central leptin more potently reduces meal frequency than meal size in the rat - Eric P. Zorrilla; Koki Inoue; Glenn R. Valdez; Antoine Tabarin; George F. Koob (Psychopharmacology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Pepper yellow mosaic virus, a new potyvirus in sweetpepper, Capsicum annuum - A. K. Inoue-Nagata; M. E. N. Fonseca; R. O. Resende; L. S. Boiteux; D. C. Monte; A. N. Dusi; A. C. de ávila; R. A. A. van der Vlugt (Archives of Virology, 2002)

Genetic identification of two distinct DNA polymerases, DnaE and PolC, that are essential for chromosomal DNA replication in Staphylococcus aureus - R. Inoue; C. Kaito; M. Tanabe; K. Kamura; N. Akimitsu; K. Sekimizu (Molecular Genetics and Genomics, 2001)

Use of a reduced‐gravity model to evaluate present and past primary productivity in the tropical open ocean - Itsuki C. Handoh; Grant R. Bigg; Masamichi Inoue (Limnology and Oceanography, 2001)
Upwelling predicted by a reduced‐gravity model is compared with remotely sensed primary productivity data through the tropical Atlantic and Pacific. The model upper layer thickness, an indicator of vertical motion, is correlated with primary productivity. We suggest that the Atlantic basin is more efficient than the Pacific in its production for the same degree of upwelling. This is a characteristic of the tropical Pacific ecological provinces being featured by low salinity in the western tropics and high nutrient, but low chlorophyll in the eastern equatorial region. A comprehensive relationship between model upper layer thickness and primary productivity is established through the tropical basins, with emphasis on the equatorial strip. Our work has implications for the application of reduced‐gravity models to estimate productivity in palaeocean studies.

Karyotype analysis of Nicotiana kawakamii Y. Ohashi using DAPI banding and rDNA FISH - R. Nakamura; S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2001)

High-resolution genetic mapping of the saccharin preference locus (Sac) and the putative sweet taste receptor (T1R1) gene (Gpr70) to mouse distal Chromosome 4 - Xia Li; Masashi Inoue; Danielle R. Reed; Taufiqul Huque; Ralph B. Puchalski; Michael G. Tordoff; Yuzo Ninomiya; Gary K. Beauchamp; Alexander A. Bachmanov (Mammalian Genome, 2001)

Enterobacter cowaniisp. nov., a New Species of the Family Enterobacteriaceae - Kohaku Inoue; K. Sugiyama; Y. Kosako; R. Sakazaki; S. Yamai (Current Microbiology, 2000)

Hematite in pyrophyllite ore deposits, Shobara district, southwestern Japan - M. Ohkawa; Y. Yamashita; M. Inoue; R. Kitagawa; S. Takeno (Mineralogy and Petrology, 2000)

Exercise- and methylcholine-induced sweating responses in older and younger men: effect of heat acclimation and aerobic fitness - Y. Inoue; George Havenith; W. Larry Kenney; Joseph L. Loomis; Elsworth R. Buskirk (International Journal of Biometeorology, 1999)

Immunolocalization of two ligninO-methyltransferases in stems of alfalfa (Medicago sativa L.) - Rossio Kersey; Kentaro Inoue; Karel R. Schubert; Richard A. Dixon (Protoplasma, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Oculomotor sequence learning: a positron emission tomography study - R. Kawashima; J. Tanji; K. Okada; Motoaki Sugiura; Kazunori Sato; Shigeo Kinomura; Kentaro Inoue; Akira Ogawa; Hiroshi Fukuda (Experimental Brain Research, 1998)

Pyruvate alleviates toxic effects of ethanol on cells in culture - K. Fukaya; M. Miyazaki; H. Pu; B. Katayama; Y. Inoue; R. Ohashi; C. Nakamura; M. Namba (Archives of Toxicology, 1997)

Sucrose consumption in mice: Major influence of two genetic Loci affecting peripheral sensory responses - Alexander A. Bachmanov; Danielle R. Reed; Yuro Ninomiya; Masashi Inoue; Michael G. Tordoff; R. Arlen Price; Gary K. Beauchamp (Mammalian Genome, 1997)

Efficacy of an ultrashort-acting β-adrenoceptor blocker (ONO-1101) in attenuating cardiovascular responses to endotracheal intubation - A. Kitamura; A. Sakamoto; T. Inoue; R. Ogawa (European Journal of Clinical Pharmacology, 1997)

Physical and genetic maps of the human herpesvirus 7 strain SB genome - G. Dominguez; J. B. Black; F. R. Stamey; N. Inoue; P. E. Pellett (Archives of Virology, 1996)

Restriction endonuclease mapping and molecular cloning of the human herpesvirus 6 variant B strain Z29 genome - G. J. Lindquester; N. Inoue; R. D. Allen; J. W. Castelli; F. R. Stamey; T. R. Dambaugh; J. J. O'Brian; R. M. Danovich; N. Frenkel; P. E. Pellett (Archives of Virology, 1996)

Characterization of the beta-lactamase from Klebsiella pneumoniae - E. E. Stobberingh; R. Okamoto; M. Inoue; S. Mitsuhashi (Antonie van Leeuwenhoek, 1985)